Cloning and function analysis of ZmICE1a, a contributor to the melioration of maize kernel traits - Yifei Xiao; Liang Tu; Yulin Jiang; Pengfei Liu; Xiangyang Guo; Angui Wang; Yunfang Zhu; Xuefeng Lu; Zehui Chen; Xun Wu (Plant Signaling & Behavior, 2025)
Kernel traits are important factors in determining maize yield. Gene mining and clarification of relevant gene functions associated with kernel traits is beneficial for breeding high-yield maize varieties. In our previous research, a critical quantitative trait locus (QTL), qKWEI3.1, associated with kernel weight was mapped using a maize F2:3 population derived from the parental lines SCML0849 and ZNC442. In the present study, qKWEI3.1 was fine-mapped, the ZmICE1a gene was cloned, and the relevant functions of ZmICE1a were dissected. The results showed that plants overexpressing ZmICE1a exhibited a shorter reproductive period, increased plant height, greater stem diameter, higher photosynthetic efficiency, and meliorated kernel traits. Transcriptome analysis revealed that ZmICE1a overexpression mediated differentially expressed genes (DEGs) such as SNRK2–10, the E3 ubiquitin-protein ligase AIP2, Pho1, and Pho2. Gene ontology and KEGG pathway enrichment analyses revealed that the DEGs were involved in the abscisic acid signaling pathway, starch, and sucrose metabolism. These results suggest that ZmICE1a is a critical, positive regulator promoting plant growth and meliorating kernel traits. The findings of this study have important implications for the improvement of grain yield through the application of genetic engineering in maize breeding.